Study On Efficacy Of Autologous Platelet Rich Plasma On Split Thickness Skin Graft Donor Site - kumar S, Sanjay; Kumar K, Senthil; Kumar T, Dinesh; Poorani, P Akshaya (Journal of Neonatal Surgery, 2025)
Background: Optimal management of split-thickness skin graft (STSG) donor sites is essential to promote healing, minimize pain, and reduce complications. Traditional paraffin gauze dressing has long been used, but recent advancements have introduced autologous platelet-rich plasma (PRP) as a promising alternative due to its regenerative properties. Objective: To compare the efficacy of autologous Platelet rich plasma (PRP) versus Paraffin gauze dressing on Split Thickness Skin Grafting donor site in terms of Speed of wound healing. Methodology: In this Comparative study, patients requiring STSGs were divided into two groups: PRP group (n=18) and non-PRP (n=18). The efficacy of autologous Platelet rich plasma (PRP) versus Paraffin gauze dressing on Split Thickness Skin Grafting donor site in terms of Speed of wound healing with respect to age, Diabetes and smoking status were compared. Results: The mean & SD of age among the patients are 48 ± 18 years and male patients (69.4%) were more than the female patients (30.06%). On comparing the two groups, patients in the PRP group had a higher healing rate than the patients in the Non-PRP group and found to be significant (0.043). Patients who were in PRP group with >40 years of age, diabetic, and smoker also had an increased healing rate. Conclusion: Autologous PRP dressing is a superior alternative to paraffin gauze for STSG donor site management, offering enhanced healing, better pain control, and improved patient comfort.